2021
DOI: 10.1016/j.metabol.2020.154439
|View full text |Cite
|
Sign up to set email alerts
|

Moderate alcohol consumption is associated with advanced fibrosis in non-alcoholic fatty liver disease and shows a synergistic effect with type 2 diabetes mellitus

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 21 publications
3
48
0
4
Order By: Relevance
“…Further research is needed to explore this finding. Lastly, liver damage slows alcohol elimination (Cederbaum, 2012), and we found that higher fibrosis scores were associated with increased odds of PEth sensitivity, consistent with a recent study (Blomdahl et al, 2020). However, fibrosis is frequently the result of high levels of alcohol consumption, so this finding may instead or in part reflect residual confounding by underreported alcohol use.…”
Section: Discussionsupporting
confidence: 91%
“…Further research is needed to explore this finding. Lastly, liver damage slows alcohol elimination (Cederbaum, 2012), and we found that higher fibrosis scores were associated with increased odds of PEth sensitivity, consistent with a recent study (Blomdahl et al, 2020). However, fibrosis is frequently the result of high levels of alcohol consumption, so this finding may instead or in part reflect residual confounding by underreported alcohol use.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, in this research, none or minimal alcohol consumption was linked with a reduced risk of incident T2DM in subjects without FLD, but not in those with FLD [70]. On the other hand, moderate alcohol consumption correlates with extensive fibrosis in non-alcoholic FLD, exhibiting a synergistic effect with T2DM [71].…”
Section: Linkage Of Alcohol Consumption With Type 2 Diabetes Mellitusmentioning
confidence: 45%
“…It has also been demonstrated that both these causes together can intensify disease progression to more severe liver disease and liver cancer. [33][34][35][36] In such mixed cases, it can be difficult to identify the leading cause, and it seems fair to indicate both NAFLD and ALD. This helps avoid focusing on and treating only one of the causes.…”
Section: Nafld Nafl Nash Cirrhosismentioning
confidence: 99%
“…At the population level, the combination of alcohol and obesity increases the probability of developing NAFLD and increases the severity of liver disease, reflecting a synergistic effect. 33,36,[228][229][230][231] A large cohort study from the U.S. reported that patients with NAFLD who drank more alcohol than the threshold of > − 3 drinks/day for men and > − 2 for women, were 3x more likely to have advanced fibrosis than those with NAFLD alone. 34,228 In addition, overall mortality was higher in adults with NAFLD who consumed excess alcohol.…”
Section: Tips On Managing Fatiguementioning
confidence: 99%